Sobre a incidência da esterilidade em vacas no estado de Minas Gerais - Megale, Francisco (Revista Ceres, 1945)
In this paper the author describes several cases of infertility in cows, observed at the State of Minas Gerais (Brasil). The clinical observations include cases of brucelosis, persistance of corpus luteus, ovarian cysts, metritis, cervicites, vaginitis, uterine and vaginal prolapses, free-martin, recto-vaginal fistules, deviation of the cervix and hypophosphorosis.